The integration of quality management system in construction industry - Nyomek, Lydia (2010)
Malaysian construction industry is facing problems to assure the construction quality due to the increasing demand in quality of delivered product. Therefore, Malaysian construction industry must impose on higher quality product to compete aggressively both at regional or international industry. The concept of quality management system has been introduced to the construction industry to control the product quality and continually improve the effectiveness and efficiency of its performance. The main thrust of a quality management system is to define the processes that will lead to the quality of end result or product. However, the implementation of quality management system is often treated independently within an organization and this contributes to the limitation of the system. With regards to the current system that has been implemented independently, the concept of integrated quality management system is introduced. Integrated quality management system is a combination of various quality management systems such as Environmental Management System and Occupational Safety and Health Management System into one coherent management system. The main aim of this study is to review the potential of applying integrated management system to construction industry. The methodologies adopted for this study are interviews with expert panel, conducting case studies and questionnaire survey. Hence, the results of study are important for the construction industry that wishes to enhance their end product quality and performance. It is found that there is a strong potential in applying integrated quality management system. Indeed this study has found that there are few construction companies have implemented this integrated system. The main challenges for applying this system are higher initial cost and lack of understanding of the concept.